Analysis of academic administrators' attitudes: annual evaluations and factors that improve teaching. Issue 3 (4th May 2017) - Cherry, Brian D.; Grasse, Nathan; Kapla, Dale; Hamel, Brad
ABSTRACT: This article examines academic administrators' attitudes towards the academic evaluation process in the US and those factors that are utilised to improve teaching. We use path regressions to examine satisfaction with evaluation procedures, as well as the direct and indirect effects of these factors on perceptions of whether the evaluation process facilitates quality instruction. With increased pressure for accountability being placed on higher education, it is important to ensure that we are meeting both public and academic expectations. The evaluation process is an important tool to ensure the university's goals and values are articulated and that academics can be successful in their individual career paths. The problem is most research finds flaws with the current method of evaluation, and academics and academic administrators are sceptical about the process and results. We find there are environmental factors that influence academic administrators' perceptions of academic evaluations and the ability to improve classroom instruction.